Respuesta :

Answer: Third option

[tex]-u-v = <-2, -3>[/tex]

Step-by-step explanation:

We have the vector u and the vector v. We must perform the operation [tex]-u-v[/tex].

To perform this operation multiply the vector u by -1 and multiply the vector v by -1.

If u = (-5,6)

So

-1u = (5, -6)

If v = (7, -3)

So

-1v = (-7, 3)

Then the sum of both vectors is done by adding the components of u with the components of v.

[tex]-u-v = (5, -6) + (-7,\ 3)\\\\-u-v = (5-7\ ,\ -6 + 3)\\\\-u-v = (-2,\ -3)[/tex]